The association between rheumatoid arthritis and periodontitis - Leech, Michelle T.; Bartold, P.M. (Best practice & research. Clinical rheumatology, 2015)
The relationship between rheumatoid arthritis and poor oral health has been recognised for many decades. The association between periodontal infection and the risk of developing RA has been the subject of epidemiological, clinical and basic science research in recent times. Converging and reproducible evidence now makes a clear case for the role of specific periodontal infective pathogens in initiating, amplifying and perpetuating rheumatoid arthritis. The unique enzymatic properties of the periodontal pathogen Porphyromonas gingivalis and its contribution to the burden of citrullinated peptides is now well established. The impact of localized infection such as periodontitis in shaping specific anti-citrullinated peptide immune responses highlights a key area for treatment, prevention and risk assessment in rheumatoid arthritis.